Optimizing micro propagation of artemisia dracunculus using tissue culture and growth regulators - Jawad Shakir Kadhim (Journal of Kerbala for Agricultural Sciences, 2025)
The tarragon (Artemisia dracunculus) is on one of the most important medicinal plants that has a useful role in the field of pharmacy. The aim of this study was production of micro propagation the tarragon plant by applying the plant tissue culture technique in establishing vegetative branch cultures. The first experiment included testing the ability of NaOCl at different concentrations and durations to sterilize the explant used as a starting point for establishing tissue cultures, the second experiment included testing different concentrations of BA and NAA at concentrations of (0, 1, 1.5) mg L-1 and (0, 0.1) mg L-1 respectively for the establishment of tissue cultures, the third experiment included testing two types of cytokinines BA and 2IP at concentrations of (0, 1, 2, 3) mg L-1 and (0, 0.1, 0.2, 0.3, 0.4) mg L-1 respectively with presence of a fixed concentration of NAA 0.1 mg l-1 for the purpose of multiplying shoot cultures. The 1% concentration of the sterilizing substance NaOCl at the 15 minute period achieved the lowest contamination rate of 0% without affecting the vitality of the explant, The results of the second experiment included the superiority of the concentration of 1.5 mg L-1 BA in achieving the highest response rate of 65%, while the concentration of 0.1 mg L-1 NAA achieved the highest response rate of 60.33%, The results of the third experiment included the superiority of BA at the concentration of 2 mg L-1 in achieving the highest rate of branch number, lengths, and fresh and dry weight of the vegetative system, which reached 35.21 branch plant-1, 4.54 cm, 3.16 mg, and 1.05 mg respectively. While the 2IP achieved the highest rates of branch number and fresh and dry weights of the vegetative system at the concentration of 0.3 mg L-1 which reached 31.05 branch plant-1, 2.83 mg, and 0.93 mg, respectively, the highest rate of branch length was at the concentration of 0.2 mg L-1 which reached 3.31 cm.